University branding: different roles of brand personality and satisfaction - Nonik Kusuma Ningrum; Ratih Kusumawardani; Ignatius Soni Kurniawan (Jurnal Siasat Bisnis, 2020)
This study aims to provide an integrative framework that investigates the effect of brand experience on loyalty that is mediated by brand personality and satisfaction in the context of an Indonesia’s private university branding. This study applies an explanatory quantitative research method using purposive random sampling as the sampling technique. The data is collected from a total of 385 students of a private university in Yogyakarta using questionnaires. A rigorous analysis of the structural equation model is used to analyze and interpret the data. The result shows that brand experience has no direct effect on brand loyalty, however it has indirect on satisfaction and simultaneously through brand personality and satisfaction. This means that students of a private university perceived that satisfaction is the most important aspect on building loyalty. This study implies that private universities should improve students’ satisfaction to gain loyalty, and consider university brand experience and brand personality in order to strengthen students’ satisfaction toward the university. Building loyalty is important because it can lessen the vulnerability of university in facing competition, not only with local but also with overseas universities or branch of the world's best university to come to Indonesia in the future.